Subdividing the Trefoil by Origami. (10th January 2013) - Langer, Joel C.; Singer, David A.
Abstract : In 2005, David Cox and Jerry Shurman proved that the curves they call m -clovers can be subdivided into n equal lengths (for certain values of n ) by origami, in the cases where m = 1, 2, 3, and 4. In this paper, we expand their work to include the 6-clover.